Pengaruh Literasi Keuangan Syariah Terhadap Preferensi Pengusaha Muslim dalam Memilih Bank Syariah: Studi Kasus di Himpunan Pengusaha Persatuan Islam - Ridwan Ibnu Asikin; Udin Saripudin; Iwan Permana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The presence of Islamic banks amidst conventional banking is an alternative banking system solution for Muslims in Indonesia who need or want to obtain banking services without having to violate the principles of Islamic law. Law No. 10 of 1998 concerning banking, this law aims to be nationally comprehensive. The government reissued Law No. 21 of 2008 concerning Islamic banking in detail defining and understanding Islamic banks specifically in Indonesia, regulating institutions, units, Islamic business activities, as well as the methods and processes for implementing Islamic bank business activities and Islamic business units. The purpose of this study is to analyze the level of Islamic financial literacy, analyze the preferences of Muslim entrepreneurs in choosing Islamic banks, and analyze the influence of Islamic financial literacy on the preferences of Muslim entrepreneurs in choosing Islamic banks in the Association of Islamic Entrepreneurs. The research method used is a quantitative method with a descriptive approach and verification of simple linear regression analysis, the sample used is all members of the Association of Islamic Entrepreneurs (HIPPI) as many as 100 respondents. This study concludes that the increase in Islamic financial literacy Based on the results of the study there is a very strong relationship between the financial literacy variable and the preferences of Muslim entrepreneurs, From the R Square value it is known that it is 0.699 or 69.9%. So it can be said that the Islamic Financial Literacy variable has an influence on the preferences of HIPPI Muslim entrepreneurs in choosing Islamic banks by 69.9% while the remaining 30.1% is influenced by other variables not included in this study.